The pivotal role of mammalian target of rapamycin inhibition in the treatment of patients with neuroendocrine tumors. (18th August 2016) - Phan, Alexandria T.; Dave, Bhuvanesh
Abstract : Mammalian target of rapamycin (mTOR) and components of the mTOR pathway play pivotal roles in neuroendocrine tumor (NET) pathogenesis. mTOR inhibition as backbone therapy within the NET treatment landscape is an ongoing focus. Data evaluating the clinical benefits of agents targeting mTOR and related pathways (alone and in combination) in the treatment of patients with pancreatic NET continues to emerge, and many of the findings to date are encouraging. Abstract: Significant advances have been made toward understanding the biology of neuroendocrine tumors (NET) in terms of defining prognosis and improving clinical management; however, many unmet needs remain. The treatment landscape for NET has evolved, with the approval of the targeted agents everolimus and sunitinib for the treatment of advanced pancreatic NET in 2011 followed by the approval of everolimus for the treatment of advanced nonfunctional gastrointestinal and lung NET in 2016. Mammalian target of rapamycin (mTOR) and components of the mTOR pathway play pivotal roles in NET pathogenesis. Effects of the mTOR inhibitor everolimus have been well documented in preclinical and clinical studies, both as monotherapy and combination therapy. mTOR inhibition as backbone therapy within the NET treatment landscape is a focus of continuing research, which includes evaluation of the growing armamentarium of approved and investigational agents as potential combination partners. Data evaluating the clinical benefits of agents targeting mTOR and related pathways (alone and in combination) in the treatment of patients with NET continue to increase. Many of the findings to date are encouraging.